Effect of Oxygen Tension on In Vitro Maturation of Buffalo Cumulus Oocyte Complexes - R Patel, Meet; S Parikh, Suryakant; S Suthar, Vishal; H Parmar, Kiran; Jhala, Dwani; D Pranami, Ruchir; V Hun, Munja (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study investigated the effect of oxygen (O2) tension during in vitro maturation (IVM) of buffalo cumulus oocyte complexes (COCs).  Buffalo ovaries (n=337) were collected from a slaughterhouse of Ahmedabad Municipal Corporation, Ahmedabad. A total of 801 COCs  were retrieved using aspiration method using 18 G 1.5’ needle and 5 mL syringe. The COCs were graded into four groups based on  cumulus layers. Two IVM conditions were compared: a benchtop incubator with 5% O2 and a conventional incubator with ambient O2 (20%). The COCs of the first three grades were randomly allocated to two groups and the effect on IVM was evaluated using chi square  test. The 5% O2 group exhibited a higher maturation rate (89.00%, 365/410) compared to the 20% O2 group (73.66%, 288/391), though  the difference was not statistically significant (p=0.21). The findings suggest that lower O2 tension during IVM may enhance COCs  maturation, potentially improving embryo development outcomes.
Keywords: Benchtop incubator; Buffalo oocytes; Conventional incubator; IVM; O2 tension